A case of maxillary sinus carcinoma: An occult aggressive entity - -, Khairunnisa; Khanum, Nishath; Basappa, Srisha Basappa; Kanwar, Santosh (Indian Journal of Case Reports, 2018)
Carcinoma of the maxillary sinus is a rare aggressive entity. Squamous cell carcinoma of maxillary sinus has the highest incidence among the tumors developing within the sinonasal compartment and has one of the worst outcomes in comparison with other head and neck tumors. Management of these tumors often presents an uphill task to clinicians. In the present case, the patient presented with a swelling in the left cheek region with a history of trauma and altered sensation and no other signs and symptoms. Based on the history and clinical examination, a provisional diagnosis of infraorbital fracture was given. Further, radiographic and histopathological evaluation was done which leads to the final diagnosis of squamous cell carcinoma of the left maxillary sinus. As oral physicians, we come across diseases of the maxillary sinus; thereby, complete assessment of any pathology of the sinuses may help in early diagnosis of this deadly disease.